Some new results for αβ-statistical convergence through difference compact operator of fuzzy 2- normed spaces - Mohammed, Elaf Hussein (JOURNAL OF ADVANCES IN MATHEMATICS, 2024)
The research aims to provide advanced compact for order αβ-converge of statistic in the normed spaces of fuzzy-2 and introduce universal the spaces̕ s.